Disruptive effect of midazolam on fear memory reconsolidation: Decisive influence of reactivation time span and memory age - Bustos, Silvia Gabriela (2009)
Benzodiazepine (BDZ) administered shortly after retrieval disrupts the reconsolidation of fear memory. In this research, we explored the way in which different factors that limit the emergence of such process may affect BDZ’s disruptive effect on fear memory reconsolidation. Animals were conditioned in a contextual fear paradigm; the consolidated memory was reactivated by exposure to the associated context for different periods of time that were followed by midazolam (MDZ) administration. We also studied MDZ amnesic effect after reactivating fear memories of several ages. We finally analyzed the effectiveness of different MDZ doses in preventing the reconsolidation of different age fear memories. The memory trace was disrupted following MDZ when the reactivation session lasted 3–5 min but it was not after a briefer 1-min reactivation period. Over a 10-min reactivation session, all animals gradually reduced their fear response, which indicates the emergence of the extinction process. When tested, MDZ rats exhibited a robust fear, suggesting that MDZ impaired the consolidation of extinction. In a 3-min reactivation session, MDZ (1–1.5 mg/kg) prevented the reconsolidation of recently acquired memories. A 21-day-old fear memory was only vulnerable to MDZ at a 1.5 mg/kg dose with a reactivation session of 5 and not 3 min, whereas a 36-day-old memory was only disrupted with a higher MDZ dose (3 mg/kg) regardless of the reactivation trial’s duration. This study demonstrated MDZ’s interference on fear-memory reconsolidation within a relatively short reactivation period in recently acquired memories. Over longer reexposure, MDZ disrupts the consolidation of extinction. A longer duration of the reexposure session, as well as higher MDZ doses, is required to prevent the reconsolidation process of remote fear memories.